Penerapan Model Pembelajaran ARIAS (Assurance, Relevance, Interest, Assessment, Satisfaction) Untuk Meningkatkan Aktivitas Belajar Simulasi Digital Siswa SMK Negeri 1 Sidoarjo - Nur Faridah Ilmianah (International Consortium of Education and Culture Research Studies, 2018)
The development of technology and knowledge requires critical thinking, systematic, logical, creative and willingness to cooperate effectively. The teacher is the main motor who has direct responsibility to translate the curriculum into teaching and learning activities. This study aims to (1) increase learning activity of digital simulation of students through the application of ARIAS learning model, (2) improve student digital simulation learning result through application of ARIAS learning model, and (3) application of ARIAS learning model in digital simulation learning. This research was conducted in SMK Negeri 1 Sidoarjo by using action research class (PTK) consisting of 4 stages namely stage of planing, implementation, observation and reflection. The subjects of this study are class X TE2 SMK Negeri 1 Sidoarjo consisting of 35 students, 32 male students and 3 female students. The instruments used are observation sheets of student learning activities, student learning outcomes, and interviews. The results of this study indicate an increase in average student learning activity that continues to increase starting from the prestudy stage of 1.92 in the category of activity enough, in the first cycle of 2.54 with the category aktvitas enough. Cycle II of 3.42 with good category activity and cycle III increased by 4.29 with very good category activity. For the results of the final test also experienced an increase in the average score of student learning outcomes given in each cycle end In the first cycle the average learning outcomes of students is 61.8, the second cycle of 71.59 and the third cycle of 83.86 and no students who score below 75. So that the implementation of ARIAS learning model can improve activity and student learning outcomes SMK country 1 Sidoarjo.